Endoglin – a marker of vascular endothelial cell proliferation in cancer - Kopczyńska, Ewa; Makarewicz, Roman (Contemporary Oncology/Współczesna Onkologia, 2012)
Endoglin (CD105) is an accessory receptor of transforming growth factor B. The highest synthesis, as well as expression, of endoglin has been found in vascular endothelial cells. The involvement of endoglin in angiogenesis and in angiogenesis-dependent processes has been observed. Endoglin promotes angiogenesis not only by activation of vascular endothelial cell proliferation but also by induction of the antiapoptotic pathway in hypoxic endothelial cells. The potential application of endoglin as a tumour angiogenesis marker, useful for cancer diagnostics and clinical application, is anticipated. Endoglin expression may be useful as an indicator of disease progression and helpful for estimation of recurrence and metastasis risk.